El desierto y la cuestión del territorio en el discurso político argentino sobre la frontera Sur - Navarro Floria, Pedro (Revista Complutense de Historia de América, 2002)
Argentine historiography accepts, in general terms, that the conquest of the southern territories and the subjection of its indigenous peoples were necessary for the construction of the nation State. However, the analysis of the political discourse of that period reveals a complex process, in which the military phase appeared late, and during which the ideas that nowadays are characterized as the «discourse of conquest» chrystallized only gradually. In 1867 this discourse became a political programme encapsulated in law 215, but in Sarmiento’s writings, in which it originated, there was a recognition of an alternative to the dominant perception of the problem as «desert/savages». Acceptance of that image gradually imposed a «logic of conquest» that then became the canonical version of the incorporation of the Pampa-Patagonia territory into the Argentine State.
Keywords: Argentina; conquest; frontier; political discourse; 19th century